Analisis Kebijakan Menteri Pendidikan Tentang Standar Kompetensi Lulusan dan Standar Isi PAI - Rosanita, Devi (AL-WIJDÃN Journal of Islamic Education Studies, 2016)
Curriculum is a set of lesson plans, the setting of objectives, content, and learning materials that are developed as guidance for the implementation of learning activities to achieve specific educational objectives. The curriculum that is implemented today is the Curriculum 2013. This curriculum is a refinement of the previous curriculum, the School-based Curriculum. The implementation of Curriculum 2013 is aimed at improving the students’ competence to be more analytic and requiring the teachers to be more creative and innovative during the process of learning. This paper analyzed two main core of National Standards of Education which are Standards of Graduate Competency and Standards of Content in School-based Curriculum and Curriculum 2013. Currently, the implementation of Standards of Graduate Competency for School-based Curriculum is based on Permendiknas RI No. 23 of 2006 on Standards of Graduate Competency for primary and secondary schools. Meanwhile, Curriculum 2013 refers to Permendiknas RI No. 54 of 2013 on Standards of Graduate Competency for primary and secondary schools. Besides, the implementation of Standards of Content for School-based Curriculum is based on Permendiknas RI No. 22 of 2006 on the Standards of Content for primary and secondary education. On the other hand, Curriculum 2013 refers to Permendikbud RI No. 64 of 2013 the Standards of Content for primary and secondary education. However, the complex problems lie under the Standards of Graduate Competency and Standards of Content, both in substantive and procedural factors, so these problems affect the technical implementation in the field as well. Therefore, the education’s quality in Indonesia must be enhanced by defining a clear and definite objective without disregarding the potential, geographical situation, and demographic situation, as well as the diverse socio-economic condition of the people.Keywords: Standards of Graduate Competency, Standards of Content for Islamic Education, Analysis of Policy